PENERAPAN KONSELING ISLAM UNTUK MENGATASI STRES AKADEMIK SISWA MTS MUQ PAGAR AIR - Almutia Gandhi; Evi Zuhara (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study aims to examine the effectiveness of Islamic Counseling services in reducing academic stress among students at MTsS MUQ Pagar Air Banda Aceh. The research is driven by the phenomenon of early adolescents facing a dual-curriculum burden (general and religious), which triggers physical exhaustion, concentration difficulties, and decreased learning motivation. This quantitative study utilized a pre-experimental design with a One-Group Pretest-Posttest approach. A sample of six Grade VII students was selected through purposive sampling based on high academic stress criteria. Data were collected using a validated and reliable academic stress scale and analyzed using the Paired Sample T-Test and N-Gain Score analysis. The results showed a significant decrease in academic stress scores, moving from the